2021
DOI: 10.1002/2211-5463.13137
|View full text |Cite
|
Sign up to set email alerts
|

SREBP1/FASN/cholesterol axis facilitates radioresistance in colorectal cancer

Abstract: Acquired and intrinsic radioresistance remains a major challenge during the treatment of patients with colorectal cancer (CRC). Aberrant cholesterol metabolism precipitates the development of multiple cancers. Here, we report that exogenous or endogenous cholesterol enhances the radioresistance of CRC cells. The addition of cholesterol protects CRC cells against irradiation both in vitro and in vivo. Sterol response element‐binding protein 1/fatty acid synthase (SREBP1/FASN) signaling is rapidly increased in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Meanwhile, the overexpression of SREBP-1 enhances the resistance of 5-FU through regulation of caspase-7-dependent PARP1 cleavage in CRC ( 60 ). On the other hand, radiation stimuli can rapidly increase SREBP-1/FASN signaling to cause cholesterol accumulation, cell proliferation, and cell death, suggesting that targeting the SREBP-1/FASN/cholesterol axis is a potential strategy for CRC patients undergoing radiotherapy ( 67 ). Recently, results from colon cancer cells and xenograft tumor models have demonstrated that RAS protein activator-like 1 inhibits colon cancer cell proliferation by regulating LXRα/SREBP1c-mediated SCD1 activity ( 68 ).…”
Section: Colorectal Cancermentioning
confidence: 99%
“…Meanwhile, the overexpression of SREBP-1 enhances the resistance of 5-FU through regulation of caspase-7-dependent PARP1 cleavage in CRC ( 60 ). On the other hand, radiation stimuli can rapidly increase SREBP-1/FASN signaling to cause cholesterol accumulation, cell proliferation, and cell death, suggesting that targeting the SREBP-1/FASN/cholesterol axis is a potential strategy for CRC patients undergoing radiotherapy ( 67 ). Recently, results from colon cancer cells and xenograft tumor models have demonstrated that RAS protein activator-like 1 inhibits colon cancer cell proliferation by regulating LXRα/SREBP1c-mediated SCD1 activity ( 68 ).…”
Section: Colorectal Cancermentioning
confidence: 99%
“…Ionizing radiation was found to alter the expression of several key regulators of lipogenesis, including upregulating AMPK, an upstream regulator of the key mediator of cholesterol synthesis SREBP1 for 6–24 h after irradiation (Figure 5). This alteration was accompanied by an increase in cholesterol and decrease in triacylglycerol levels 273 . Interestingly, inhibition of stress‐responsive cholesterol synthesis in glioblastoma after combination therapy with ionizing radiation and dopamine receptor antagonists did not significantly increase radiosensitivity in cell culture, but did significantly improve median survival and reduce proliferation in murine xenograft models 274 .…”
Section: Changes To Major Metabolic Pathways Induced By Ionizing Radiationmentioning
confidence: 99%
“…Inhibition of stearoyl‐CoA desaturase 1 (SCD1), the rate‐limiting enzyme in the formation of monounsaturated fatty acids, decreased clonogenic survival after ionizing radiation in hepatocellular carcinoma cell culture, while overexpression decreased genomic instability as measured by comet assay 272 . Additionally, radiosensitivity of hepatocellular carcinoma can be decreased by the addition of monounsaturated fatty acids 272 and radiosensitivity of cultured and xenografted colorectal cancer cells diminished by exogenous addition of cholesterol 273 . Ionizing radiation was found to alter the expression of several key regulators of lipogenesis, including upregulating AMPK, an upstream regulator of the key mediator of cholesterol synthesis SREBP1 for 6–24 h after irradiation (Figure 5).…”
Section: Changes To Major Metabolic Pathways Induced By Ionizing Radiationmentioning
confidence: 99%
“…Recently, more and more studies have reported that the SREBP1/FASN axis is also involved in cholesterol synthesis. In rectal cancer, the SREBP1/FASN signaling pathway is activated rapidly under radiation stimulation, leading to cholesterol accumulation, cell proliferation, and inhibition of apoptosis, and blocking the SREBP1/FASN pathway hinders cholesterol synthesis and accelerates radiation-induced colorectal cancer cell death, which could be a potential target for colorectal cancer therapy [ 89 ].…”
Section: Regulation Of Lipid Metabolism In the Tumor Microenvironmentmentioning
confidence: 99%